DEVELOPMENT OF OPTIMAL FUEL LOADING CONFIGURATIONS FOR ARMENIAN NPP SPENT NUCLEAR FUEL TRANSPORT CASK - Baghdasaryan, N.H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
Since transition of the fuel used in NPP from initial enrichment of 3.6% to 3.82% a necessity arises of revaluation of the security of transportation containers of spent nuclear fuel and based on it appropriate design modifications. To ensure subcriticality of containers borated steel insets are used. In this paper the results of study of optimal spatial configuration of borated and regular stainless steel guide sleeves configurations that allow meeting regulatory requirements on criticality safety. The model of the SNF transport cask was developed by KENO-VI code of SCALE 6.1 package. Isotopic composition of WWER-440 SNF was calculated by ORIGEN-S code of SCALE 6.1 package.